Offervilje. Om ret og rimelighed blandt venner og fjender og om at komme og dømme levende og døde i Max Kestners film "I am Fiction" - Jacobsen, Louise Brix; Nielsen, Henrik Skov; Kraglund, Rikke Andersen (Passage - Tidsskrift for litteratur og kritik, 2013)
Louise Brix Jacobsen, Rikke Andersen Kraglund & Henrik Skov Nielsen: “Selfsacrifice. On Right and Reasonableness among Foes and Friends, and on Judging the Living and the Dead in Max Kestner’s film I am Fiction” In 2011, the performance artist Thomas Skade-Rasmussen Strøbech lost a lawsuit against his former friend and collaborator Helge Bille Nielsen and the publishing house of Gyldendal. This led to a debate about copyright, freedom of expression, identity, and the line between fiction and reality. In 2008, Nielsen or Das Beckwerk published the novel The Sovereign where Strøbech – seemingly without his knowledge and apparently against his will – is the main character. About a year after losing the lawsuit Strøbech and film director Max Kestner gives his version of the events before, during, and after the trial in the film I am Fiction (Identitetstyveriet). This article analyzes I am fiction in order to show how the film on the one hand outlines Strøbech’s version of the events as a story about a victim but on the other hand undermines this version with humor and irony and points towards an artistic collaboration between alleged victim and villain.